‘¿Qué vamos a hacer con esas impostoras?’: Orquídeas a la luz de la luna o el fenómeno del cine a través de la máscara - López, Antonio-Sajid (Latin American Theatre Review, 2016)
The controversial play Orquídeas a la luz de la luna (1982) by Carlos Fuentes revolves around two women named María Félix and Dolores del Río. These characters adopt as their own the stories and urban legends surrounding the two icons of Mexican cinema for whom they are named. María and Dolores are convinced of these “masks,” of this semblance, which sows doubt in the public that recognizes them. Fuentes casts the public as an audience within the fiction by transforming the proscenium into an imaginary movie screen that serves as an interpretive lens of artifice. This article studies the space that is generated between the real and the seeming to show how distancing becomes a concrete element within the play and thereby facilitates the audience’s understanding of the fictional and aesthetic constructs that maintain the public masks of these two cinematographic legends.